Fixed Regression Test Day Model as a solution in predicting the genetic value of dairy cattle - Indrijani, Heni; Anang, Asep (Indonesian Animal Sciences Society, 2009)
Genetic evaluation on milk yield production basically based on breeding value. This research was addressed to study milk production curve, for the most appropriate genetic evaluation, and the best methods in estimating genetic parameter and predicting breeding values. Data were collected from PT. Taurus Dairy Farm, consisting of 581 cows having 305 days records in first lactation (P305) and 542 cows having 305 days records in second lactation. Records used for Test Day (TD) evaluation were 5,373 for first lactation, and 4,925 for second lactation. Total records used for Test Day were 10,298. The results indicated that the most suitable curve, being able to be used for genetic evaluation was Ali-Schaeffer with the coefficient of correlation of 0.999, and the most appropriate model for estimation of genetic parameters and prediction of breeding values was fixed regression model with the regression of Ali-Schaeffer by taking account to the covariates. The genetic evaluation can therefore be conducted simultaneously by ignoring lactation levels. Key Words: Test Day, Milk Production Curve, Breeding Value, Dairy Cattle